Analisis Biaya Hemodialisis pada Penyakit Ginjal Kronis: Peran Karakteristik Pasien di Rumah Sakit Regional Indonesia - Fauziah Fauziah; Ikhwan Yuda Kusuma; Bella Aisya Putri; Khamdiyah Indah Kurniasih; Gamaliel Agung Nugroho; Fiqih Nurkholis (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Haemodialysis (HD) is the primary treatment for end-stage renal disease in Indonesia and heavily strains the national health insurance. This study examined how patient characteristics influence the direct medical costs of CKD patients receiving HD at Dr. R. Goeteng Taroenadibrata Regional General Hospital. A retrospective cross-sectional analysis was conducted using secondary data from medical, pharmacy, and financial records between July and December 2023. The study included 85 patients who met the inclusion criteria. Statistical analyses were performed using IBM SPSS Statistics, and cost differences across patient characteristics were analysed using nonparametric tests. The total cost over six months reached IDR 2.64 billion, averaging IDR 654,758 per HD visit. While no significant cost differences were observed across patient characteristics such as age, gender, comorbidities, or HD frequency (p > 0.05 for all), descriptive data indicated higher average costs in older patients, in patients receiving HD weekly, and in patients with CKD due to non-hypertensive etiologies. These findings suggest that standard reimbursement rates may overlook variations in resource utilization, highlighting observed cost variations that suggest the need for more tailored health financing approaches. Broader, multicenter studies are recommended to improve resource allocation in CKD management.